2022
DOI: 10.3390/ijerph19127168
|View full text |Cite
|
Sign up to set email alerts
|

New Technology and Loss of Paid Employment among Older Workers: Prospective Cohort Study

Abstract: Background: This study investigates the association between the implementation of new technology in the workplace and the subsequent loss of paid employment among older workers. Methods: We estimated the prospective risk of loss of paid employment (register-based) from questions on new technology among 10,320 older workers (≥50 years). To investigate potential differences between work types, analyses were stratified by job function: (1) work with symbols (office, administration, analysis, IT), (2) work with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The register-based outcome measure, loss of paid employment, has been described previously 26 , 27 and was defined as workers no longer fulfilling the abovementioned criteria for being employed during the 2-year follow-up period from 2018 to 2020 (see ‘Study design and participants’). We truncated at the baseline age of 63 to ensure that the participants had loss of paid employment before the official state pension age, which in Denmark was 65 years in 2018 (raised to 66 in 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The register-based outcome measure, loss of paid employment, has been described previously 26 , 27 and was defined as workers no longer fulfilling the abovementioned criteria for being employed during the 2-year follow-up period from 2018 to 2020 (see ‘Study design and participants’). We truncated at the baseline age of 63 to ensure that the participants had loss of paid employment before the official state pension age, which in Denmark was 65 years in 2018 (raised to 66 in 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Corporate resilience is defined as the capacity of an enterprise to swiftly adapt, adjust, and restore its normal operations amid internal and external disruptions, uncertainties, and changes, exhibiting principally low volatility and consistent growth. Prior research has corroborated that digitization can bolster enterprise resilience (ER), empowering companies to more effectively adapt to alterations and respond to uncertainties [11]. Regarding the reduction in corporate volatility through digitization, firstly, digitization can enhance the visibility and transparency of the supply chain [10].…”
Section: Mediating Effect Of Enterprise Resilience 251 Digitization A...mentioning
confidence: 99%
“…A report from the International Labour Organization indicated that prior to the advent of COVID-19, the stability of the youth labor force was already precarious. Moreover, the onset of COVID-19 intensified the economic crisis, leading to an escalation in unemployment rates [10,11]. In the context of the global economy's tepid recovery and the inconsistent fluctuations in labor market supply and demand, the employment landscape is confronting grave challenges, necessitating the immediate establishment of stable and sustainable employment trajectories.…”
Section: Introductionmentioning
confidence: 99%